The Ability of Prospective Mathematics Teachers in Preparing TPACK Integrated Student Worksheet - Gunawan, Rendi; Sridana, Nyoman; Hayati, Laila; Subarinah, Sri (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2025)
Student worksheet made by prospective mathematics teachers many have not integrated TPACK. By mastering the understanding of TPACK, teachers can create interesting, innovative and quality learning. This study aims to describe the ability of prospective mathematics teachers in compiling the TPACK integrated student worksheet in terms of the feasibility of content, language, presentation, and graphics. This type of research is a quantitative descriptive research with the research sample being Mathematics Education students who are taking Micro Teaching courses, namely classes 6B3 and 6E2 totaling 14 people. The sampling technique was carried out by purposive sampling technique. The data of this study was obtained from the results of the observation of the TPACK integrated student worksheet compiled by prospective mathematics teachers. The data obtained was analyzed by descriptive analysis techniques. Based on the results of the research, the ability of prospective mathematics teachers in compiling the TPACK integrated student worksheet aspect in the aspect of content eligibility was obtained a percentage of 86% with a high category, the language aspect was obtained a percentage of 92% with a high category, the presentation aspect was obtained a percentage of 85% with a high category and the graphic aspect was obtained a percentage of 84% with a medium category. Overall, it can be concluded that the ability of prospective mathematics teachers in compiling the TPACK integrated student worksheet has a high category with a percentage of 86.75%.